2014
DOI: 10.1590/0004-282x20140098
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of children and adolescents with epilepsy: analysis of clinical and neuropsichological aspects

Abstract: Epilepsy compromises the development of cognitive and social skills and represents a risk of psychiatric comorbidity. Objective: To compare psychopathological symptoms in children with epilepsy and in a healthy group, and to correlate the results with neuropsychological and clinical variables. Method: Forty five children with idiopathic epilepsy and sixty five healthy controls underwent neuropsychological evaluation and their caregivers replied to a psychopathology questionnaire (Child Behavior Checklist -CBCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The study by Moreira et al ( 51 ), however, suggested no relationship between emotional and behavioral problems and other clinical variables (duration of epilepsy or number of ASMs), but highlighted a significant relationship with children IQ. It would, therefore, be interesting, in a future research, to add this parameter in our analysis.…”
Section: Discussionmentioning
confidence: 94%
“…The study by Moreira et al ( 51 ), however, suggested no relationship between emotional and behavioral problems and other clinical variables (duration of epilepsy or number of ASMs), but highlighted a significant relationship with children IQ. It would, therefore, be interesting, in a future research, to add this parameter in our analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Another study of our group, analysing the same sample using the Child Behavior Checklist (CBCL) found worse results in psychopathology in children with epilepsy with certain psychopathological variables related to IQ (sluggish cognitive tempo, aggressive behavior, attention problem and activities) and academic performance (conduct, breaking rule behavior and school), also with no relation to clinical variables 29 . The complexity of these relations and the multifactor nature of cognitive dysfunction in epilepsy seem to turn the implemented methodology (cross-sectional) too limited to confirm a causal relationship between attention deficit and epilepsy versus comorbid ADHD.…”
mentioning
confidence: 77%
“…Studies have revealed that epileptic children are susceptible to severe deficits in memory [9,10,11,12,13,14] and academic achievement [15,16] compared to healthy control group. Severe psychological deficits have also been found among epileptic children compared to healthy control group [17,18,19,20]. Extent studies have also revealed that patients with low socioeconomic status experience more psychological and cognitive deficits compared to those with high socioeconomic status [5,21,22].…”
Section: Introductionmentioning
confidence: 97%